Penegakan Hukum Tindak Pidana Pemalsuan Surat Tanah oleh Penyidik Ditreskrimum Polda Maluku Utara - Fahrian Nurhidayat; Hervina Puspitosari (Lembaga Pengembangan Kinerja Dosen, 2024)
The crime of falsifying land certificates is an unlawful act that intends to take over the rights to land ownership from the victims. This land certificate forgery case is a rare or little case encountered by the General Criminal Investigation Directorate of the North Maluku Regional Police because so far the cases that have been entered are from reports of people who are victims of land certificate forgery. The purpose of this study is to know and analyze the form of law enforcement in the criminal act of land certificate forgery and also find out what are the obstacles experienced by police investigators of the Directorate of General Criminal Investigation of the North Maluku Regional Police when carrying out their duties as well as with efforts made by police officers, especially investigators to overcome obstacles in law enforcement of land certificate forgery crimes. The method used is in the form of an empirical juridical method with primary data sources that the author found through interviews with members as well as auxiliary investigators at the General Criminal Investigation Directorate of the North Maluku Regional Police along with secondary data. With data analysis methods in the form of qualitative analysis methods, where data obtained through collection methods such as interviews with resource persons and observation of reality in the field which will then be drawn conclusions. It should be noted that law enforcement in the crime of forgery of land certificates still has many obstacles such as loss of evidence, long summoning of witnesses, search and seizure permits and low legal error in the community.